2013
DOI: 10.1016/s1734-1140(13)71492-0
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of naringin on cyclosporine (A) induced nephrotoxicity in rats: Involvement of hemeoxygenase-1

Abstract: Abstract:Background: Clinically, chronic nephrotoxicity may lead to renal functional impairment and progress to end stage renal failure. The renoprotective effect of a flavonoid naringin (NG) against cyclosporine A (CsA)-induced nephrotoxicity was investigated in this study. Methods: Nephrotoxicity was induced in male albino Wistar rats by injecting 25 mg/kg body weight of CsA for a period of 21 days. CsA-induced rats were also cotreated with 40 mg of NG/kg body weight, orally. Results: After the experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
3
8
0
Order By: Relevance
“…Lin et al [36], add that naringenin upregulates hemeoxygenase enzyme expression in renal tissues maintaining its level and then it reduces renal oxidative stress damage and its oxidative parameters such as malondialdehyde "MDA" and nitric oxide. Chandramohan and Parameswari [26], are also in consistent with our results for an improvement in renal histopathological and ultra-structural changes, cyclosporine blood level, renal functions and redox status parameters due to concurrent use of naringenin and cyclosporine.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Lin et al [36], add that naringenin upregulates hemeoxygenase enzyme expression in renal tissues maintaining its level and then it reduces renal oxidative stress damage and its oxidative parameters such as malondialdehyde "MDA" and nitric oxide. Chandramohan and Parameswari [26], are also in consistent with our results for an improvement in renal histopathological and ultra-structural changes, cyclosporine blood level, renal functions and redox status parameters due to concurrent use of naringenin and cyclosporine.…”
Section: Discussionsupporting
confidence: 92%
“…There was a significant gain in the rats' body and kidney weight of third group which received naringenin with cyclosporine because of antioxidant effect of naringenin that counteracts effects of cyclosporine induced oxidative stress such as the weight loss in consistent with a previous study [26], but this is in contrast with a study [27] who reported that naringenin reduces the body weight gain based on its insulin-like properties that correct many metabolic disturbances linked to the insulin resistance without any effect on the appetite. There was also a significant gain in the rats' body weight of fourth group, which received an olive oil with cyclosporine in comparison with the second group, which received cyclosporine only, and the third group, which received naringenin with cyclosporine in consistent with [28] who reported that long-term ingestion of virgin olive oil produces weight gain and insulin resistance.…”
Section: Discussionsupporting
confidence: 90%
“…However, side effects associated with CsA treatment are numerous and kidney dysfunction is the main complication of CsA treatment. 30 This study demonstrated that allicin administration attenuated renal damage in rats treated with CsA. The protective effects of allicin may be multifactorial involving regulatory effects on inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 68%
“…The therapeutic effect of EPO‐BMSCs is higher than that of EPO and BMSCs. The rat model of CsA‐induced nephrotoxicity is a well‐defined and highly reproducible model . In vivo, however, EPO‐BMSCs showed higher ability to improve renal function than BMSCs; the CsA‐induced rats treated with EPO‐BMSCs exhibited fewer interstitial lymphocyte infiltrates, less tubular swelling, less necrosis and atrophy, and lower levels of interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Acute or chronic CsA-induced nephrotoxicity leads to renal function impairment and histopathological and ultrastructural damages. [2][3][4][5] In recent years, several studies have reported that mesenchymal stem cell (MSC) transplantation can prevent or attenuate drug-induced renal injury, [6][7][8] but their effect in CsA-induced nephrotoxicity is not clear.…”
Section: Introductionmentioning
confidence: 99%